PENERAPAN MODEL PEMBELAJARAN GAMIFIKASI DALAM PEMBELAJARAN MENULIS TEKS CERPEN BERORIENTASI DIKSI KONOTATIF PADA MEDIA NEARPOD FASE F SMA PASUNDAN 3 BANDUNG - Alifa Angel Ivada; Panca Pertiwi Hidayati; Adi Rustandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research is motivated by students low understanding in writing short stories particularly those orientes toward connotative diction. One of the contributing factors is the lack of innovative and engaging learning models implemented by teacher. Therefore, this study aims to examine the effectiveness of the gamification learning model in improving students ability to write short stories with a focus on connotative diction. Specifically, the objectives of thus research are: 1) to describe students writing abilities before and after being taught using the gamification model and nearpod media in writing short stories oriented toward connotative diction; 2) to illustrate the differences in writing abilities between students taught using the expository model and those taught using the gamification model in teaching short story writing focused on connotative diction at SMA Pasundan 3 Bandung. The research method used is an experimental method with a control group. The fidings show a significant improvement in the experimental class, with an average pretest score of 44 increasing to 90 in the posttest. Meanwhile, the control class also showed improvement, with the average pretest score rising from 38 to 76 in the posttest. These results indicate that the gamification learning model is effective in enhacing students skills in writing short stories with connotative diction orientation